2019
DOI: 10.1109/jstsp.2019.2901170
|View full text |Cite
|
Sign up to set email alerts
|

Securing Downlink Massive MIMO-NOMA Networks With Artificial Noise

Abstract: In this paper, we focus on securing the confidential information of massive multiple-input multipleoutput (MIMO) non-orthogonal multiple access (NOMA) networks by exploiting artificial noise (AN).An uplink training scheme is first proposed with minimum mean squared error estimation at the base station. Based on the estimated channel state information, the base station precodes the confidential information and injects the AN. Following this, the ergodic secrecy rate is derived for downlink transmission. An asym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 38 publications
(58 reference statements)
1
56
0
Order By: Relevance
“…One of the aims of this letter is to introduce a system architecture to further reduce the OP in MIMO‐NOMA structures. Beamforming and OP in mmWave massive MIMO systems have been discussed in Zeng et al In this paper, it is shown that the proposed system outperforms the conventional massive MIMO‐OMA.…”
Section: Introductionmentioning
confidence: 79%
“…One of the aims of this letter is to introduce a system architecture to further reduce the OP in MIMO‐NOMA structures. Beamforming and OP in mmWave massive MIMO systems have been discussed in Zeng et al In this paper, it is shown that the proposed system outperforms the conventional massive MIMO‐OMA.…”
Section: Introductionmentioning
confidence: 79%
“…Figure shows the averaged secrecy rate scriptCs for 1 cluster vs the signal‐to‐noise ratio (SNR), showing the effect of π := π α − π κ on the search region . In this figure, our scheme with and without SWIPT is compared with the OMA one and even the exhaustive search method and Reference . Moreover, the effect of AN coding is also considered on the security.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In Figure , EE is evaluated for our proposed scheme as iiP, compared to Reference and the traditional Dinkelbach method . Our proposed precoding design completely outperforms the existing work.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Under this assumption, we obtain the lower bound on the achievable system secrecy rate due to the unfavourable scenario regarding the eavesdropping capacity. Recent research shows that actually the inter-user interference can help enhance information transmission security of NOMA networks in the presence of passive eavesdropper [31]. How it affects the secrecy performance of our considered NOMAassisted MEC networks is an interesting direction to pursue in the future work.…”
Section: Apmentioning
confidence: 95%